An onion farmer with a case of hypersensitivity pneumonitis caused by Aspergillus niger. (2018) - Sakamoto, Tomohiro; Yamasaki, Akira; Funaki, Yoshihiro; Harada, Tomoya; Okazaki, Ryota; Hasegawa, Yasuyuki; Sueda, Yuriko; Fukushima, Takehito; Morita, Masahito; Yamamoto, Akihiro; Kodani, Masahiro; Shimizu, Eiji
Abstract: A 62-year old man was admitted to our hospital with a 2-week complaint of a dry cough, general fatigue, and dyspnea on effort. He has been an onion farmer for several years and developed these symptoms after cleaning up onion peels with air compressors. A chest roentgenogram and computed tomography showed a ground glass shadow in the bilateral upper lung field. Cellular analysis of the bronchoalveolar lavage fluid showed elevated total cell numbers and lymphocytes. Transbronchial lung biopsies revealed a non-caseating granuloma with both epithelioid cells and Langhans giant cells. After the admission, these symptoms and radiological findings gradually improved without any treatment. Then, a returning-home provocation test was positive only when he worked cleaning up onion peels with air compressors. A. niger was cultured from his workplace and black mold from the onion peels. The precipitation antibody and the antigen were both positive for Aspergillus . Therefore, we diagnosed this case as hypersensitivity pneumonitis caused by inhalation of A. niger . Although hypersensitivity pneumonia caused by A. niger is rare, physicians should aware the possibility of this condition in farmers because A niger is ubiquitously present in several vegetables and fruits.